Diversity, equity, and inclusion (DEI) management - Wasieleski, David; Weber, James (Business and society 360., 2024)
The Business and Society (BAS) 360 book series is an annual publication targeting cutting-edge developments in the broad business and society field, such as stakeholder management, corporate social responsibility and citizenship, business ethics, sustainability, corporate governance and others. Each volume will feature a comprehensive discussion and review of the current 'state' of the research and theoretical developments in a specific business and society area. Volume 6 focuses on Diversity, Equity, and Inclusion management, examining the origins, trends, and future direction of DEI.